Prognostic value of post-discharge depression in patients recently hospitalized with acute heart failure - Li, Junlei; Jiang, Chao; Liu, Rong; Lai, Yiwei; Li, Li; Zhao, Xiaoyan; Wang, Xiaofang; Li, Ling; Du, Xin; Ma, Changsheng; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2022)
Background: Depression is a prevalent comorbidity in patients with heart failure (HF). However, data regarding the prognostic significance of depression during the early post-discharge period in patients hospitalized with acute HF regardless of left ventricular ejection fraction (LVEF) were scarce. Methods and results: The Heart Failure Registry of Patient Outcomes (HERO) study is a prospective, multi-center study of patients hospitalized with acute HF in China. At the first follow-up after discharge (median 4.0, interquartile range [IQR]: 2.4–6.1] weeks), depressive symptoms over the past 2 weeks were assessed using the Patient Health Questionnaire-9 (PHQ-9). Of 3,889 patients, 480 (12.3%) had depression (PHQ-9 score ≥10). A total of 3,456 patients (11.4% with depression) were included in the prospective analysis. After a median follow-up of 47.1 weeks (IQR: 43.9, 49.3) from the first follow-up, 508 (14.7%) patients died, and 1,479 (42.8%) patients experienced a composite event (death or HF rehospitalization). Cox proportional hazards models were used to assess the association of post-discharge depression with adverse events. After adjustment, post-discharge depression was associated with an increased risk of all-cause mortality (hazard ratio [HR] 2.38 [95% confidence interval (CI): 1.93–2.94]; p<0.001) and the composite event (HR 1.78 [95% CI: 1.55–2.05]; p<0.001). A per scale point increase in PHQ-9 score (ranging from 0 to 27 points) was associated with a 7.6% increase in all-cause mortality (HR 1.08 [95% CI: 1.06–1.09]; p<0.001). In the sub-group analysis, the association between depression and the composite event was significantly stronger in relatively younger patients (<75 vs. ≥75 years; p for interaction=0.011), and the association between depression and all-cause mortality was significantly stronger in patients with preserved ejection fraction than in those with reduced ejection fraction (p for interaction=0.036). Conclusion: Post-discharge depression in patients recently hospitalized with acute HF is associated with an increased risk of adverse events, regardless of left ventricular ejection fraction. Screening for depressive symptoms during the early post-discharge period may help to better identify high‐risk patients and tailor patient management. Further studies are needed to determine how regular depression screening can help improve patient management and clinical outcomes.